PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) TERINTEGRASI KEISLAMAN UNTUK MELATIH KEMAMPUAN LITERASI MATEMATIKA PADA MATERI ARITMETIKA SOSIAL KELAS VII SMP - Sa'adah, Umi Lailatus; Utami, Mutiara Arlisyah Putri (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2025)
The research aimed to develop a Student Worksheet (LKPD) integrated with Islamic values to train mathematical literacy skills in social arithmetic for Year 7 secondary school students, ensuring it was both feasible and practical. The study was conducted in Year 7 at MTs Darul Falah Banyuwangi. The research method employed was Research and Development (R&D) using the ADDIE development model, which encompassed the stages of analysis, design, development, implementation, and evaluation. During the analysis stage, data were collected on initial problems in mathematics education. The design stage involved the process of designing the Student Worksheet to be developed. The development stage consisted of producing the product based on the design that had been previously created, adjusted according to feedback and validation by expert validators. Once the product was deemed feasible, the implementation stage followed, where the developed product was applied in the learning process. The final stage, evaluation, involved assessing the tested product to determine its practicality. The data collection techniques employed included interviews and questionnaires. The data analysis technique used involved calculating the percentage of feasibility and practicality. The product evaluation was carried out by five expert validators: subject matter experts, media experts, evaluation experts, integration experts, and learning experts. The research findings revealed that the developed product had an average feasibility percentage of 91.04%, categorised as highly feasible. Additionally, the findings indicated that the product had an average practicality percentage of 87.48%, also categorised as highly practical for use.